Evaluation of decellularized xenogenic porcine auricular cartilage as a novel biocompatible filler. Issue 7 (10th February 2018) - Shin, Sung‐Chan; Park, Hee Young; Shin, Nari; Jung, Da‐Woon; Kwon, Hyun‐Keun; Kim, Ji Min; Wang, Soo‐Geun; Lee, Jin‐Choon; Sung, Eui‐Suk; Park, Gi Cheol; Lee, Byung‐Joo
Abstract: Fillers are products that fill the space in soft tissues of the human body and actively used in the various medical fields. Unfortunately, most of the cost‐effective commercially available fillers are synthetic and have limitations in terms of their biocompatibility. Here, we evaluated the possible application of decellularized xenogenic cartilage as a long‐lasting material for soft tissue augmentation and compared it with two commercially available fillers Artesense (polymethylmethacrylate microspheres) and Radiesse (calcium hydroxyapatite [CaHa]). To do so, porcine auricular cartilage was harvested, followed by freezing and grinding of the tissue into flakes. Then, we used 1% Triton X‐100 to decellularize the flakes. We then, respectively, injected 0.1 cc of each material (decellularized xenogenic cartilage, Radiesse, and Artesense) into the subcutaneous layer at three different sites per subject in 12 Sprague‐Dawley rats, and evaluated the inflammatory cell infiltration and foreign body reactions of each. Our data indicate that the infiltration of giant cells in the injection area was significantly lower in the decellularized xenogenic cartilage injection group than that in the Radiesse and Artesense injection groups. Further, we observed some neutrophil infiltration in the xenogenic cartilage and Artesense injection groups at 1 month, but these levels were much lower at 3 months (comparable to the Radiesse injection group). Thus, decellularized xenogenic cartilage may have a distinct advantage in terms of biocompatibility compared with other commercial injectable long‐lasting fillers, making it one of the most feasible, natural, and cost effective materials in the market. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2708–2715, 2018.